Identification of Streptococcus pneumoniae: development of a standardized protocol for optochin susceptibility testing using total lab automation - Burckhardt, Irene; Panitz, Jessica; Zimmermann, Stefan (BioMed research international, 2017)
Purpose. Optochin susceptibility is one parameter used in the laboratory to identify Streptococcus pneumoniae. However, a single standardized procedure does not exist. Optochin is included neither in the current EUCAST breakpoint tables nor in the CLSI performance standards for antimicrobial susceptibility testing. We wanted to establish an evidence-based protocol for optochin testing for our Total Lab Automation. Methods. We tested seven different agars and four different reading time points (7 h, 12 h, 18 h, and 24 h). To accommodate for serotype diversity, all tests were done with 99 different strains covering 34 different serotypes of S. pneumoniae. We calculated a multivariable linear regression using data from 5544 inhibition zones. Results. Reading was possible for all strains at 12 h. Agar type and manufacturer influenced the size of the inhibition zones by up to 2 mm and they varied considerably depending on serotype (up to 3 mm for serotype 3). Depending on agar and reading time point, up to 38% of inhibition zones were smaller than the cut-off of 14 mm; that is, the result of the test was false-negative. Conclusions. Shortening incubation time from 24 h to 12 h for optochin susceptibility testing is feasible. Agar and incubation time have to be chosen carefully to avoid false-negative results.